1990
DOI: 10.1111/j.1399-3054.1990.tb05688.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light quality (blue, red) and fluence rate on the synthesis of pigments and pigment‐proteins in maize and black pine mesophyll chloroplasts

Abstract: Maize (Zea mays L. hybrid ZP‐704) and black pine (Pinus nigra Arn.) were grown for five days at low fluence rate (0.4–4.0, μmol m–2 s−1) in blue or red light. Compared to red light of the same fluence rate, blue light effects in maize were repressive for the accumulation of Chita, b, carotenoids and light‐harvesting complex‐2 (LHC‐2) proteins. The maximal reduction of proteins bound to the light‐harvesting complex of photosystem 2 and pigments was attained at different fluence rate levels. In black pine, blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…It is tempting to speculate that this peculiar behavior of S. viridis is linked to its C4 metabolism, but there are actually not many other reports that we are aware of to confirm this idea. In one report, though, it was shown that, in maize, blue light represses the accumulation of chlorophylls, compared to red light (58), which seems consistent with our observations. On a different level, it is noteworthy that this effect on chlorophyll in S. viridis was not revealed by color indices such as TGI, illustrating the limitations of non-destructive color proxies.…”
Section: Species-specific Behaviorssupporting
confidence: 93%
“…It is tempting to speculate that this peculiar behavior of S. viridis is linked to its C4 metabolism, but there are actually not many other reports that we are aware of to confirm this idea. In one report, though, it was shown that, in maize, blue light represses the accumulation of chlorophylls, compared to red light (58), which seems consistent with our observations. On a different level, it is noteworthy that this effect on chlorophyll in S. viridis was not revealed by color indices such as TGI, illustrating the limitations of non-destructive color proxies.…”
Section: Species-specific Behaviorssupporting
confidence: 93%
“…It is tempting to speculate that this peculiar behavior of S. viridis is linked to its C4 metabolism, but information on this topic is scarcely available in the literature. In one report on maize, though, it was shown that blue light represses the accumulation of chlorophylls, compared to red light [ 52 ]. Concerning the lack of correlation between TGI and chlorophyll estimates, one explanation might be that S. viridis plants started flowering during the gradient treatment, and TGI may have been biased by the presence of paler green panicles, independently of the variations in leaf chlorophyll content.…”
Section: Resultsmentioning
confidence: 99%